2020
DOI: 10.1038/s41598-020-70839-9
|View full text |Cite|
|
Sign up to set email alerts
|

Fatty acid synthase, a novel poor prognostic factor for acute lymphoblastic leukemia which can be targeted by ginger extract

Abstract: Altered metabolism of fatty acid synthesis is considered a hallmark characteristic of several malignancies, including acute lymphoblastic leukemia (ALL). to evaluate the impact of fatty acid synthase (FASN) on drug resistant ALL, bone marrow samples were collected from 65 pediatric ALLs, including 40 de novo and 25 relapsed patients. 22 non-cancer individuals were chosen as controls. Quantitative RT-PCR showed increased expression levels of FASN in drug resistant patients compared with the therapy responders. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…It was previously declared that ROS may cause DNA damage, contributing to p53 activation followed by apoptosis 34,35 . Interestingly, FASN overexpression is recently introduced by our group as a negative prognostic factor for paediatric ALL 24 . Additionally, the association of FASN with resistance to chemotherapeutic drugs was previously determined 36 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It was previously declared that ROS may cause DNA damage, contributing to p53 activation followed by apoptosis 34,35 . Interestingly, FASN overexpression is recently introduced by our group as a negative prognostic factor for paediatric ALL 24 . Additionally, the association of FASN with resistance to chemotherapeutic drugs was previously determined 36 .…”
Section: Discussionmentioning
confidence: 97%
“…Fatty acid synthase (FASN) is another key regulator which may be responsible for leukaemia drug resistance. According to our previous study FASN expression levels are upregulated in ALL drug resistant children, and they may be reduced by cells treating with ginger extract 24 . It would be interesting to know which ginger derivative could play role in the FASN molecular pathway.…”
Section: Introductionmentioning
confidence: 98%
“…Upon hypoxic stress, different cancer cells had different cell-type-specific regulation of FASN, increased, decreased or unaffected [ 42 ]. A recent paper reported that FASN was upregulated in relapsed ALL patients; moreover, FASN inhibition may help to overcome glucocorticoid resistance [ 43 ]. FASN inhibition may sensitize AML cells to differentiation therapy [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, glucocorticoids such as prednisone and dexamethasone can inhibit the expression of FASN and thereby inhibit the proliferation and growth of tumor cells ( 71 ). At the same time, the study found that ginger extract can inhibit the expression of FASN, and combined use with dexamethasone can enhance the drug sensitivity of ALL cells to dexamethasone ( 72 ). The combination of bezafibrate and medroxyprogesterone acetate ( 39 ), orlistat ( 73 ), N-phenylmaleimide ( 74 ) and methyl jasmonate ( 75 ) can all regulate the expression of FASN to inhibit the growth of tumor cells.…”
Section: Fa Metabolism In Hematological Malignanciesmentioning
confidence: 99%